Effect of Discipline, Work Motivation and Incentive on Employee Effectiveness - Ani Santika, Veny; Syarief, Faroman (Green Publisher, 2022)
Article Literature Review of the Effects of Discipline, Work Motivation and Incentives on Employee Work Effectiveness is a scientific article that aims to build hypotheses in research that can influence between variables that will be used in further research, within the scope of Human Resource Management. The method in writing this Literature Review article is to use the library research method, sources obtained from online media such as Google Scholar, Mendeley and other academic online media. In the results of this literature review obtained regarding the factors that can influence Employee Work Effectiveness in the company. These factors include: (1) Discipline influences employee effectiveness (2) Work motivation influences employee effectiveness (3) Incentives influence employee effectiveness